INVESTIGATING LOCAL MOTORCYCLISTS DECISION TO USE ELECTRIC MOTORCYCLES DOMINATED TRAFFIC ENVIRONMENT REGION - I Made Dwi Budiana Penindra; Dewa Made Priyantha Wedagama; I Gusti Ngurah Priambadi; Anak Agung Istri Agung Sri Komaladewi; I Ketut Suarsana (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study seeks to understand the factors that influence local motorcyclists in Bali to adopt electric motorcycles (e-MCs). Earlier research highlighted several research gaps, including differences in people's readiness to switch, inconsistent findings regarding the effects of environmental concern, and variations in the influence of government support across regions. Based on these gaps and local characteristics, the research looks at how motorcyclists in the SARBAGITA region in Bali view the idea of moving to e-MCs. By collecting data from local motorcyclists and using structural equation modeling (SEM), a model was created to analyze the behavior of adopting e-MCs, leading to nine hypotheses—eight of which were confirmed. The study results show motorcyclists in Bali are influenced by various factors when considering a switch to e-MCs, including government policies, risk perceptions, and pricing. Improved conditions and government support enhance switching intentions, while high effort expectations and perceived risks act as barriers. Interestingly, ease of use doesn't always lead to higher adoption rates, and environmental concerns have minimal impact. The study emphasizes the need for better infrastructure and pricing strategies, highlighting the importance of hedonic motivations in Bali's tourism context. Bali government subsidies could lower costs, and enhance charging facilities, while raissing public awareness can further encourage e-MC adoption. The findings highlight also the importance of contextual and psychological factors in technology adoption, suggesting that policy incentives alone are insufficient without supporting infrastructure and risk mitigation. The study is limited to local motorcyclists and does not include domestic or international tourists.